Silage quality of Brachiaria brizantha cultivars ensiled with different levels of millet meal - Costa,K.A.P (2011)
The silage quality of Brachiaria brizantha cultivars ensiled with different levels of millet meal was evaluated. The experimental design was a completely randomized with three replications in a factorial 3 x 4, with three cultivars of Brachiaria brizantha: marandu, xaraés, and piatã and four levels of millet meal 0, 5, 10, and 15%. The addition of millet meal improved the quality of B. brizantha silage. The inclusion of the additive at 15% provided the best nutritional values. The piatã silage had the lowest contents of neutral detergent fiber, acid detergent fiber, and lignin and the highest content of total digestible nutrients, being a better quality silage as compared to those of xaraés and marandu grasses.